Strategies for Increasing Profitability and Sustainability of The Leather Tanner Industry with without Interesting Capital Structure - Kurniawan, Aceng (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
The bankruptcy of the leather tanning industry in Sukaregang Garut was mostly caused by a decrease in profitability due to an increase in the capital structure with an increase in external loans with an interest system. The purpose of this research is to determine the strategy for increasing the profitability and sustainability of the leather tanning industry with an interest-free capital structure. The data collection method was carried out by interviewing leather tanning industry players. The data obtained were analyzed using profitability ratio analysis, EEI and Altman Z-Score to determine the level of business continuity. There are three strategies for increasing the profitability and sustainability of the tanner industry, namely the strategy of interest-free loans, partnerships and strategies for increasing price and quality. From the analysis of the profitability ratio of the partnership strategy is the chosen strategy, the results of calculating the COGS per ft2 show that the partnership strategy is a strategy that has a fixed COGS value. Based on the results of the EEI analysis, all strategies for increasing the profitability and sustainability of the tannery industry are in the range of 0-1, meaning that the leather industry is Affordable but not sustainable, but the highest and most stable EEI value of all these strategies is the partnership strategy. The results of the sustainability analysis using the Altman Z-Score method show that the partnership strategy is the strategy that has the most high business sustainability value with a healthy status.